Caiçara song and its roots - Macedo, Bruno Tavares (Em Perspectiva, 2024)
My research at PPGH / UFF (A Literary Festival and a Cultural Silo in Paraty, 1975-2015) makes a history of the organized actions of the actors linked to the social issues experienced in Paraty in the period. This historical moment is analyzed within a perspective of cultural transformation due to the accelerated flow of people and information in the region. Not only due to the conflicts caused by the construction of the Rio Santos road, but also due to changes in political relations and their collective manifestations, their social practices and their representations in discourses produced in Brazilian poetry and song.